Integration of Zeolite Membrane Bioreactor With Granular Sludge-Based Anammox in High-Efficiency Nitrogen Removal From Iron Oxide Red Wastewater - Feng, Xing-Hui; Wang, Xiao-Jun; Li, Hai-Xiang; Zhang, Hai-Ya; Zhu, Zong-Qiang; Liang, Yan-Peng; Dong, Kun; Zeng, Hong-Hu (Frontiers in Microbiology, 2022)
Acquisition of stable nitritation and efficient anammox play crucial role in partial nitritation (PN) combined with anammox for the nitrogen removal from ammonium-rich wastewater. Due to the limitation of AOB enrichment and NOB control in traditional MBR can result in a lower nitrite production rate (NPR) and unstable PN, eventually reducing the nitrogen removal rate (NRR) via PN-anammox. In this study, we developed a zeolite membrane bioreactor (ZMBR) to enhance the PN of iron oxide red wastewater (IORW), in which the biofilm derived from zeolite surface can provide a free ammonia (FA)-containing microenvironment for AOB enrichment and NOB inhibition. Result showed that ZMBR can tolerate higher influent nitrogen loading rate (NLR) of 2.78 kg/(m3·d) in comparison to the traditional MBR (2.02 kg/(m3·d)), and the NPR in ZMBR and traditional MBR were 1.39 kg/(m3·d) and 0.96 kg/(m3·d), respectively. The mass concentration ratio of NO- 2-N/NH+ 4-N ranged from 1.05 to 1.33 in ZMBR, suggesting a suitable condition for the nitrogen removal via anammox. Subsequently, the domesticated granular sludge obtained from a paper making wastewater treatment was used as the carrier of anammox bacteria to remove nitrogen. After 93 days operation, the NRR was observed to be 2.33 kg/(m3·d) and high-throughput sequencing indicated that the relatively higher abundance (45.0%) of Ca. K. stuttgartiensis was detected in the granular sludge of bottom part of reactor which can produce more proteins and lipids, suggesting a good settleability. Overall, this study provides a high-efficient method to control PN and domesticate anammox for the nitrogen removal from IORW.